Magnetization and Specific Heat of La doped Sr2FeMoO6 - Tovar, Manuel (2004)
We present high-temperature magnetization and low-temperature specific heat measurements performed on the electron doped double perovskite Sr 1.7La0.3FeMoO6. We have obtained the electronic contribution to Cp, γ=11.5(5)mJ/molK2. The electronic susceptibility, derived from the magnetic measurements in the paramagnetic regime (T>Tc=390K), was χe 0=(4.9±1.5)×10-4emu/mol. Antiferromagnetic coupling between localized and itinerant moments was inferred from the data, with a coupling constant λ=-(475±50)mol/emu, that results in a ferromagnetic-like Curie-Weiss susceptibility with Θ=390(5)K. These results are compared with those obtained for the undoped material. © 2003 Published by Elsevier B.V.